Post-Quantum Cryptography and the Future of Data Security: Challenges, Migration Readiness, and Strategic Protection of Information Systems - Seham Ahmed Daraz; Ziaulhaq Dhau Obeid (Surman Journal of Science and Technology, 2025)
This study examines post-quantum cryptography as a future-oriented approach to protecting data security against the expected risks of quantum computing. It explains that current public-key cryptographic systems, such as RSA and elliptic-curve cryptography, may become vulnerable when powerful quantum computers are developed. The study highlights that organizations need to prepare early for migration to quantum-resistant cryptographic systems. This preparation requires more than technical updates; it involves cryptographic inventory, risk assessment, cybersecurity governance, vendor coordination, staff training, and strategic planning. The main focus of the study is to analyze how organizational readiness affects the successful adoption of post-quantum cryptography. The proposed framework includes factors such as awareness of quantum threats, maturity of cryptographic inventory, governance readiness, vendor readiness, technical infrastructure flexibility, and cybersecurity expertise. The study concludes that post-quantum cryptography is essential for protecting sensitive data in the future. Successful migration depends on early planning, institutional readiness, and the adoption of NIST-approved post-quantum standards.